EFEKTIVITAS PROBLEM BASED LEARNING PADA PEMBELAJARAN CERITA BAHASA INDONESIA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SD (JS (JURNAL SEKOLAH), 2026)
Abstract: Critical thinking ability is a skill that students must have in learning Indonesian. This study aims to analyze the effectiveness of the Problem Based Learning (PBL) learning model in improving students' critical thinking skills in learning Indonesian story material at SD Muhammadiyah Alam Surya Mentari. The study used a quasi-experimental method with a Nonequivalent Control Group Design involving two classes, namely the experimental class given PBL treatment and the control class using conventional learning. Data collection was carried out through pretest, posttest, observation, and documentation. The results showed that the average posttest score of the experimental class (79.5) was higher than the control class (64.25). The t-test showed a Sig. value